Teach this poem. Volume I, The natural world - Holzer, Madeleine Fuchs; Academy of American Poets (New York, NY : Routledge and The Academy of American Poets, 2024)
"Instill a love of poetry in your classroom with the illuminating and inviting lessons from Teach This Poem. Co-published with the Academy of American Poets, the leading champion of poets and poetry in the US, this book is an accessible entry-point to teaching poetry and fostering a poetic sensibility in the classroom. Each lesson follows a consistent format, with a warm-up activity to introduce the chosen poem, pair-shares, whole class synthesis, related resources, oral readings, and extension activities. Curated by the AAP, the poems are chosen with an eye toward fostering compassion and representing diverse experiences."--
Keywords: Poetry -- Study and teaching; LANGUAGE ARTS & DISCIPLINES / Literacy; POETRY / American